2020
DOI: 10.3390/biomedicines8080283
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Anticoagulation and Diabetes Do Not Inhibit the Angiogenic Potential of Hypoxia Preconditioned Blood-Derived Secretomes

Abstract: Patients suffering from tissue ischemia, who would greatly benefit from angiogenesis-promoting therapies such as hypoxia preconditioned blood-derived secretomes commonly receive oral anticoagulation (OA) and/or have diabetes mellitus (DM). In this study, we investigated the effect of OA administration on the in vitro angiogenic potential of hypoxia preconditioned plasma (HPP) and serum (HPS), prepared from nondiabetic/diabetic subjects who did not receive OA (n = 5) or were treated with acetylsalicylic acid (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 91 publications
(137 reference statements)
2
16
0
Order By: Relevance
“…Hypoxia preconditioned blood-derived secretomes represent a new generation of autologous growth factor preparations [23][24][25][26][27][28]30] that can be produced through extracorporeal conditioning of peripheral blood cells (PBCs) under wound-simulating conditions, namely physiological temperature and hypoxia [25,26]. We had previously demonstrated that hypoxia preconditioned plasma (HPP) and serum (HPS) supply angiogenesis-specific signaling, similar to that naturally In this experiment we included adipose-derived cell suspension (ADCS), a secretome with lymphangiogenic properties [34], and fetal calf serum (FCS), a powerful lymphangiogenic stimulator [10], as positive controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypoxia preconditioned blood-derived secretomes represent a new generation of autologous growth factor preparations [23][24][25][26][27][28]30] that can be produced through extracorporeal conditioning of peripheral blood cells (PBCs) under wound-simulating conditions, namely physiological temperature and hypoxia [25,26]. We had previously demonstrated that hypoxia preconditioned plasma (HPP) and serum (HPS) supply angiogenesis-specific signaling, similar to that naturally In this experiment we included adipose-derived cell suspension (ADCS), a secretome with lymphangiogenic properties [34], and fetal calf serum (FCS), a powerful lymphangiogenic stimulator [10], as positive controls.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation was carried out for 4 days (blood incubation time), without any prior centrifugation. Pericellular (local) hypoxia (~1% O 2 ) was generated in situ through cell-mediated O 2 consumption, by controlling the blood volume per unit area (BVUA > 1 mL/cm 2 ) in the blood-containing syringe, and consequently, the PBC seeding density [25,29,30]. After 4 days, the blood was passively separated into three layers, from bottom to top: red blood cell (RBC) component, buffy coat/clot, and HPP/HPS, so that the top layer comprising hypoxia preconditioned plasma or serum could be filtered (0.2-µm pore filter, Sterifix ® , Braun AG, Melsungen, Germany) into a new syringe, removing cells/cellular debris.…”
Section: Preparation Of Blood Plasma/serum and Hypoxia Preconditionedmentioning
confidence: 99%
See 2 more Smart Citations
“…In this Special Issue, we invited research and review papers in various areas of oxygen biology research that focused on the fundamental understanding of HIF signaling pathways and related gene expression profiling, as well as pharmacogenomic biomarkers, molecular targets driving the regulation of human physiology and pathophysiology, and validation in animal models. As a result, we published six original papers and three review articles in this Special Issue [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
mentioning
confidence: 99%